Adoptive versus Mixed Families: Child Adjustment, Parenting Stress and Family Environment - Santos-Nunes, Marta (2018)
Recent research in adoption has considered the factors and processes that underlie the adjustment of children and families. However, little research has been conducted on certain types of adoptive families, specifically on families with both adoptive and biological children often designated as mixed families. This subject is addressed by the present study which also analyzes the association between the type of adoptive family and children’s outcomes—prosocial and problem behavior— parenting stress and the relational family environment. It also examines whether children’s gender, age at adoption and the number of children in the home moderate these effects. 102 parents of adoptive children (ACF) 33 parents of both adoptive and biological children (ABCF) and 102 parents of biological children (BCF) participated in the study. Target-children were aged from 6 to 12 years. The Portuguese versions of the SDQ-P, PSI-SF and FES (Interpersonal Relationship dimension) were used. Results showed that the type of adoptive family—ACF and ABCF—significantly explained the variance of children’s behavioral problems and parenting stress. The child’s gender was shown to moderate the relationship between ACF parents and their perception of child’s prosocial behavior. The results give relevant clues as to the importance of distinct outcomes in adoptive families—ACF and ABCF—compared to families with only biological children and should, therefore, be a resource for professionals involved in the adopters’ suitability assessment and adoption intervention.